If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(7x + -4) + 4x + -5 = -1 Reorder the terms: -1(-4 + 7x) + 4x + -5 = -1 (-4 * -1 + 7x * -1) + 4x + -5 = -1 (4 + -7x) + 4x + -5 = -1 Reorder the terms: 4 + -5 + -7x + 4x = -1 Combine like terms: 4 + -5 = -1 -1 + -7x + 4x = -1 Combine like terms: -7x + 4x = -3x -1 + -3x = -1 Add '1' to each side of the equation. -1 + 1 + -3x = -1 + 1 Combine like terms: -1 + 1 = 0 0 + -3x = -1 + 1 -3x = -1 + 1 Combine like terms: -1 + 1 = 0 -3x = 0 Solving -3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-3'. x = 0 Simplifying x = 0
| 6-10x=39-17x | | -144=-12x | | -(6x-4)+4x-6=-2 | | 11.4(x+3)+2=4.5(x+1) | | 5n-2n=-9 | | -12*12= | | 2.625=fraction | | 5=5+2m+3m | | 12*-12= | | 7(-16)(0)(-3)= | | Y=-25+4(x+5) | | x+x+4+3(x)+7=71 | | 1x+8=8x+22 | | 9x=3y-6 | | 13x+5=1x+11 | | 0.5a+2=5 | | 9x+15=3x+17 | | Y=10+3(x-5) | | x+x+4+3timesx+7=71 | | -3+x=-38 | | 2x+8=1x+3 | | 2x+6+x=90 | | P=2(33)+2(20) | | -6x-23=36 | | -4+(-8)-16-(9)= | | -5x-12=15 | | Y=-13+4(x+2) | | 4-x=-2x-7 | | 2(2y-7)+2y=106 | | x=2(20)-7 | | Y=30-2(x+3) | | -8+(-6)+20= |